COMPUTATIONAL ANALYSIS OF TRADITIONAL ARCHITECTURAL ELEMENTS IMPACT ON AI-GENERATED DESIGNS - Deran Jin; Mohd Zairul; Sarah Abdulkareem Salih (Operational Research in Engineering Sciences: Theory and Applications)
Artificial intelligence technology and related industries have flourished in recent years, and the application of AI-generated design in architectural design has become more and more widespread. At the same time, today's society has higher and higher requirements for modern architectural design. In contrast, traditional architectural elements contain national characteristics and regional features and carry the excellent history and culture of humanity. In order to effectively inherit the superb culture, optimize architectural design, and promote the progress of modern architecture, it is imperative to integrate traditional architectural elements into modern architectural design. Based on this, the main research goal of this paper is to combine traditional architectural elements and modern architectural design with the help of computer neural network technology so as to make the contemporary architectural design style more diversified in order to provide more architectural design methods and architectural design concepts for the relevant staff.